Pengaruh Lingkungan Kerja dan Budaya Organisasi terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Mediasi:Studi pada Bank Majalengka - Uki, Masduki; Alan Rusdiana; Moch. Febri Sayidil Umam; Pipih Sopiyan (Coopetition : Jurnal Ilmiah Manajemen, 2026)
This study aims to analyze the influence of work environment and organizational culture on employee performance, with organizational commitment as a mediating variable, at Bank Majalengka. A quantitative approach was employed using a survey of all 149 permanent employees, and the data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results show that the work environment has a significant effect on organizational commitment with a path coefficient of 0.319 (t = 3.984; p = 0.000), while organizational culture has a stronger effect on commitment with a coefficient of 0.488 (t = 7.316; p = 0.000). Organizational culture also directly affects employee performance (coefficient = 0.309; t = 3.171; p = 0.002), as does organizational commitment (coefficient = 0.380; t = 3.313; p = 0.001). However, the work environment does not have a direct effect on performance (coefficient = -0.162; t = 1.817; p = 0.070), but exerts an indirect effect through organizational commitment (mediation coefficient = 0.121; t = 2.570; p = 0.010), indicating full mediation. Additionally, organizational commitment partially mediates the relationship between organizational culture and performance (mediation coefficient = 0.185; t = 2.761; p = 0.006). The R² value for employee performance is 0.568, indicating that 56.8% of the variance in performance is explained by the model. These findings underscore the critical role of organizational commitment as a psychological mechanism linking internal organizational factors to employee performance.